2012
DOI: 10.1038/ki.2011.345
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of microRNA miR-146a correlates with the development of chronic renal inflammation

Abstract: MicroRNAs (miRNAs) are highly conserved small non-coding RNAs that act as post-transcriptional regulators of target mRNA. In this study, we sought to identify the microRNA underlying local inflammation in a murine model of chronic kidney disease (CKD). In microarray analysis of kidneys, the expression of miR-146a/b was elevated in B6.MRLc1 CKD mice that spontaneously develop renal inflammation with age. Primary-microRNA analysis found that elevated miR-146a/b expression in the kidneys of B6.MRLc1 mice was main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
88
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 31 publications
10
88
1
Order By: Relevance
“…It has been revealed that the expression of miR-146a involves in several pathological pathways including tubular atrophy and interstitial fibrosis by infiltrating inflammatory cells such as macrophage and T cell as well as with secretion of some cytokines such as IL-1β, IL-10, and CXCL leading progressive renal inflammation (25). Similar to our study, some authors demonstrated the role of miR146a in LN pathogenesis (24). In a study by Lu et al, miR-146a is not overexpressed in LN tubulointerstitial tissue, however effectively up-regulate in glomerular tissue (24).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It has been revealed that the expression of miR-146a involves in several pathological pathways including tubular atrophy and interstitial fibrosis by infiltrating inflammatory cells such as macrophage and T cell as well as with secretion of some cytokines such as IL-1β, IL-10, and CXCL leading progressive renal inflammation (25). Similar to our study, some authors demonstrated the role of miR146a in LN pathogenesis (24). In a study by Lu et al, miR-146a is not overexpressed in LN tubulointerstitial tissue, however effectively up-regulate in glomerular tissue (24).…”
Section: Discussionsupporting
confidence: 80%
“…Similar to our study, some authors demonstrated the role of miR146a in LN pathogenesis (24). In a study by Lu et al, miR-146a is not overexpressed in LN tubulointerstitial tissue, however effectively up-regulate in glomerular tissue (24). In another study, expression of miR-146a was shown to be involved in level of inflammation and thus can determine histological activity index (25).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…49,[53][54][55] While some studies have shown lower miR-146a expression during DN, 49 others have shown higher expression. 53,54 Our results (Figures 1, 2, and 7) show a significant upregulation of miR-146a in the peritoneal macrophages as well as in the kidneys of STZ-induced diabetic mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanism for such association might be due to impaired ability to inhibit apoptosis and inflammation among GG homozygotes compared with AA homozygotes. miR-146a plays important roles in regulating the innate immunity and inflammatory responses (Rusca and Monticelli 2011;Ichii et al 2012). Aberrant expression of miR-146a has been observed in a variety of disease, including cancer, autoimmune and inflammatory diseases, and infectious diseases (Li et al 2010).…”
Section: Discussionmentioning
confidence: 99%